PEMANFAATAN LUMPUR LAPINDO SEBAGAI BAHAN SUBSTITUSI SEMEN PADA PEMBUATAN PAVING BLOCK - Anom Wiryasa, Ngk. Made; Sugita, I Nyoman; Wedasana, Agus Surya (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008, 2012)
he aim of this research was to obtain the benefits of Lapindo silt as cement substitution material in fabricating paving block with the most ideal mixture composition evaluated from compressive strength and water absorption with physical quality based on PUBI-1986. Paving block were made using Lapindo silt as cement substitution with composition that were A mixture (100% PC; 0% LS), B mixture (90% PC; 10% LS), C mixture (80% PC; 20% LS), D mixture (70% PC; 30% LS), and E mixture (60% PC; 40% LS). Fabricating process of paving block started from material preparation, making mixture, molding, curing, selection, and then followed by conducting the research by compressing the paving block and obtaining the water absorption. Based from water absorption, result of this research showed that the mix D has better benefits of Lapindo silt as cement substitution material with optimum water absorption and decreasing compressive strength. This was caused by SiO2 contained in the mixture (as filler) and also supported by CaO (as a binder between materials). The small value of water absorption can also increase the durability of paving block. The best composition was D mixture, where has optimum water absorption with little decreasing in value of compressive strength.
Keywords: paving block, Lapindo silt, pressure strength, water absorption